(untitled) (Fiep Bulletin - online, 2019)
This research aims at tracing the profile of the elderly practitioner of physical exercises in the district of Itaipava -Petrópolis. This study is important because the world age pyramid is reversing due to the accelerated growth of the elderlypopulation. Studies indicate that physical exercise is primordial in the search for healthy aging and for the maintenance of theautonomy of the elderly. Through a questionnaire, we interviewed 42 elderly men and women, aged 60 and over, seeking to knowthe general profile of this public. The study will serve as an instrument for the service providers to offer a service of excellence andto meet this profile of clients in their needs. The survey found that most of the region’s practitioners are between 60 and 65 yearsof age, are male, receive more than 9 minimum wages and have completed higher education. The most practiced activities arebodybuilding and walking, and the main goal sought by the elderly is the quality of life. The most part of the interviewed do not usepersonal trainer’s service.